Patient and treatment factors associated with survival among pediatric glioblastoma patients: A Surveillance, Epidemiology, and End Results study. (January 2018) - Lam, Sandi; Lin, Yimo; Zinn, Pascal; Su, Jack; Pan, I-Wen
Highlights: Younger age and supratentorial location were associated with improved survival. Gross total resection was associated with improved survival. Later year of diagnosis in the decade studied was associated with improved survival. Abstract: Glioblastoma (GBM) is a rare malignancy in children. The United States Surveillance, Epidemiology, and End Results (SEER) database allows large-scale analyses of clinical characteristics and prognostic features. We used it to study patients aged <20 years with histologically confirmed GBM (2000–2010) and examined the relationship between patient demographics, tumor characteristics, patterns of treatment, and outcomes. The primary outcome was disease-specific survival. 302 subjects were identified, with median age 11 years. Median follow-up was 32 months (95% CI 27–39). 34.4% had gross total resection (GTR). 61% underwent radiation after surgery (17% of subjects <3 years, 67% of those aged 4–19 years). Median survival and 2-year survival rates were 20 months and 46.9%, respectively. In multivariate analyses, age, tumor location, extent of resection, and year of diagnosis were significantly associated with the primary outcome. Compared to those aged 0–4 years, subjects aged 5–9 years and 10–14 years had higher risk of mortality. Infratentorial tumor location (HR 2.0, 95% CI 1.2–3.3, p = 0.007) and subtotal resection (HR 2.04, 95% CI 1.4–3.0, p < 0.001) were associated with increased mortality. Later year of diagnosis was significantly associated with decreased risk of death (HR 0.93, 95% CI 0.9–0.99, p = 0.031). There was no association between sex, race, region, or tumor size and the primary outcome. Repeat analyses examining all-cause mortality identified the same risk factors as for CNS cancer–specific mortality. Younger age, supratentorial location, GTR, and later year of diagnosis were associated with improved survival.